The Relation Between Aggressive Behavior and Self Esteem in Character Development - Zuana, Muhammad Mujtaba Mitra; Umayyah, Ummu; M, Dwi Bhakti Indri; Maknuun, Lu’lu’il; Hasan, Moch Sya’roni; Aprilianto, Andika; Rofiq, Ainur; Taja, Nadri; Indriana, Dina; Fauzi, Anis (International Journal of Psychosocial Rehabilitation, 2020)
Aggressive behavior is an act or behavior that is intended to harm others. Teens who have high aggressive behavior can not choose which behavior is appropriate and can not control how that will be done. Esteem (self-esteem) high will be able to provide a positive assessment of the existence itself and can protect itself from the negative influences that come from within or from outside himself. It can make teens appreciate her good-value for themselves and their environment. Esteem(self-esteem) is low allowing more to violent or aggressive behavior is often called. The purpose of this study to (1) determines the level of self-esteem (self-esteem) to students, (2) determine the level of aggressive behavior of students, and (3) determine the relationship of self-esteem (self-esteem) and aggressive behavior of students. This research is a quantitative research that is descriptive and correlational. The subjects that the research sample is class IX as many as 121 students. The sampling technique used is Simple Random Sampling. The instrument used was a questionnaire, using calling Likert models. Correlational analysis using correlation product-moment technique.The main research findings are a significant relationship with the negative direction r (count = -0.514 and r table = 0.179 at the level signification 0.05,r> count -0.514 r Table 0.179. It can be concluded that the results of correlation product-moment indicate that there is a significant relationship trending negative between self-esteem (self-esteem) and aggressive behavior Nine-grade students of SMP Negeri 02 Kediri, meaning that the higher the self-esteem (Self Esteem) owned by the students, the lower the aggressive behavior do.